Komitmen Organisasional, Tenaga Penjual, dan Tipe Kepemimpinan: Bagaimana Mengelola, Meningkatkan Komitmen dan Mempertahankan Tenaga Penjual - Wardhana, Leo Indra (PRESTASI, 2012)
Sales people are different with the other non-sales employeers. They are more independent and self-reliant. In the other hand, the turnover rate of sales people are the highest among the other jobs in generla. This high degree of turnover rate makes companies suffer from sales loss due to some costs resulting from sales peolpe turnover. Nevertheless, Recruiting and retaining high performing experienced sales people are the most difficult tasks which is faced by sales and human resource managers today. Thus, many organizations need to reevaluate their policy in managing their sales people and need to understand the personality and motivation of their sales people. This paper first shows that the type of leadership, especially transformational and servant leadership is the most suitable leadership style for sales people which possibly lower the rate of turnover of sales people and maintain profitable relationship with customer. Second, the effect of ethical climate also important in sales people retention.